Two (p)ppGpp Synthetase Genes, relA and spoT, Are Involved in Regulating Cell Motility, Exopolysaccharides Production, and Biofilm Formation of Vibrio alginolyticus - Yin, Wen-Liang; Xie, Zhen-Yu; Zeng, Yan-Hua; Zhang, Ju; Long, Hao; Ren, Wei; Zhang, Xiang; Cai, Xiao-Ni; Huang, Ai-You (Frontiers in Microbiology, 2022)
The stringent response mediated by the signal molecule (p)ppGpp is involved in response to multiple environmental stresses and control of various physiological processes. Studies have revealed that (p)ppGpp strongly affects the formation and maintenance of several bacterial biofilms. However, the specific regulatory roles of (p)ppGpp on biofilms, especially on the expression of genes related to cell motility and exopolysaccharides (EPSs) production, remain poorly understood. We recently reported two (p)ppGpp synthetase genes relA and spoT from the epizootic pathogen Vibrio alginolyticus. Herein, we found that the (p)ppGpp synthetase genes of V. alginolyticus contributed to biofilm formation at low cell density and biofilm detachment at high cell density, respectively, in polystyrene microtiter plates. Quantitative reverse transcription PCR (qRT-PCR) analysis revealed that the expression levels of both EPSs and motility associated genes were consistent with the development of biofilms. Besides, the (p)ppGpp synthetase gene spoT was found to be closely involved in the regulation of flagellum, smooth/translucent colony morphology and spotty pellicle at the air-liquid interface. Interestingly, pleiotropic phenotypes of ΔrelAΔspoT were similar to that of the rpoN (σ54) deletion mutant. Meanwhile, the absence of (p)ppGpp synthetase genes reduced the expression levels of rpoN at both low and high cell densities, suggesting that (p)ppGpp may mediate the formation and detachment of biofilm via positively affecting the alternative sigma factor RpoN. These findings allow us to propose (p)ppGpp as a crucial regulator for biofilm development in V. alginolyticus, in view of the regulatory roles of relA and spoT in cell motility and EPSs production.